Yen Loan to KLIA Project: Socioeconomic Impact on the Sepang and Bandar Enstek Area - Hassan, Asmadi; Mohd Huda, Mohd Ikbal; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2016)
In 1994, the Government of Malaysia received 61.518 million yen to commence the Kuala Lumpur International Airport (KLIA) project. The airport is located in the district of Sepang, Selangor, which was originally oil palm plantations and small villages. The construction project completed and began in used in 1998. This paper is to evaluate the impact of Japan’s ODA for Malaysia, particularly yen loan to socioeconomic. In term of socioeconomic impact, many new cities were established such as Bandar Baru Salak Tinggi, Bandar Baru Nilai, Banting, Bandar Enstek and Cyber Jaya. Similarly, new housing, schools, shopping malls and other facilities such as the Sepang International Circuit and Universiti Sains Islam Malaysia (USIM) were built. New roads connecting to the airport also completed the development of these places. In terms of employment, previously many who depended on agriculture now turned to business, hospitality, services, transportation and others. In fact, the huge investment significantly affected the surrounding population, particularly the creation of modern towns, businesses and educational centres which gave rise to various types of employment.